FILSAFAT DAN METODOLOGI ILMU EKONOMI: Kontroversi dan Perkembangannya - Wahyuddin, M. (Universitas Muhammdaiyah Surakarta, 2000)
The controversy and the development of the economics are needed to study for the sake of to know the content of the economics from time to time. The economics is a synthesis of some point of view that had been controversial between them. By the existence of the synthesis, hopefully the economics would develop widely.Moreover, there are some briefs of point of view in this article which are included in the economic view and we can observe the development of the methodology.